2013
DOI: 10.1016/j.hrmr.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based review of e-HRM and strategic human resource management

Abstract: Abstract. One stated purpose of electronic human resource management (e-HRM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
235
2
10

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(261 citation statements)
references
References 78 publications
14
235
2
10
Order By: Relevance
“…The following related studies are Rawash 2012, Al-Dmour, et. al and 2012, Khasman, et al (2015, Elhazzam (2015), Ayeta (2016), Ngai andWat, 2006 andMarler (2009).…”
Section: The Screening Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The following related studies are Rawash 2012, Al-Dmour, et. al and 2012, Khasman, et al (2015, Elhazzam (2015), Ayeta (2016), Ngai andWat, 2006 andMarler (2009).…”
Section: The Screening Methodsmentioning
confidence: 97%
“…Recruitment and selection, employee record keeping, internal and external communication respectively are the highest levels of implementation. According to the study of Marler (2009), Strong Implementation of e-HRM is identified with perceptions of strategic effectiveness of HR. It is both positive and negative perceptions.…”
Section: The Degree Of Implementation Level Of E-hrm Functionsmentioning
confidence: 99%
“…According to (Kurland and Egan, 1999;Greenberg, 1990), there are a number of factors that are related to HRM practices that influence the employee's perceptions of bias and fairness (Marler and Fisher, 2012). According to a study by (Moorman, 1991), in places where there have been good HRM practices, the employee commitment levels were almost always seen to be high, however, in organizations where the HRM practices were deemed or perceived to be unfair, then those places showed decreased commitment levels from their employees (Janssen, 2000).…”
Section: Hrm Practice and Employee Work-related Perceptionsmentioning
confidence: 99%
“…In addition, they suggested that the Chinese SEMs should consider both western practice and Chinese characteristics for better development. Marler and Fisher [4] reviewed 40 documents to examine the electronic HRM studies. They claimed that more empirical studies about electronic HRM and strategic HRM should be taken from a macro point of view.…”
Section: Introductionmentioning
confidence: 99%